The Realities and Expectations of Calculating Government Service Costs: An Analysis of Jordanian Hospitals - Alqudah, Obiedah Mohammad; Salleh, Safrul Izani Mohd (International Journal of Economics and Financial Issues, 2023)
The goal of this study is to look at how government service expenses are calculated and analysed in Jordanian hospitals to direct health spending in the hospitals of the ministry of health of Jordan for 2021. ABC systems encourage hospitals to use, improve, and evolve in order to save government spending. The theoretical analysis’s most significant conclusions were that the process of computing service costs was wrong and did not rely on the cost accounting system of activities or others. Furthermore, the calculation technique has resulted in a significant disparity in the cost of calculating each service from one hospital to the next, proving the inadequacies of the calculation approach. The study indicates that the Health Activity-Based Costing System (ABC) be activated to monitor expenditures, especially medical and healthcare disposables, in order to decrease waste costs; that pay-outs on the system be linked to high involvement files; and that an inventory is conducted at the close of every year to guarantee that the stock fits actual spending.